Speakers’ choice of apology strategies in a discourse completion task: A study of Turkish speakers in Tabriz - Javid Fereidoni; Kosar Kheiri; Nafiseh Tadayyon Chahartagh (زبان پژوهی)
This study investigates the use of apologizing strategies by speakers of Azerbaijani Turkish in Iran. One hundred and twenty (60 male and 60 female) randomly selected speakers of Azerbaijani Turkish from Tabriz participated in a Discourse Completion Test (DCT) and returned 2400 apology speech acts. The DCT included 20 scenarios representing 10 discourse situations. The acts were analyzed based on the categorization suggested by Blum-Kulka and Olshtain (1984), which included Illocutionary Force Indicating Device, Taking on responsibility, Explanation, Offer of repair, Promise of forbearance, Concern for the hearer, and Nonverbal strategies. The findings indicated that the highly preferred apology strategies among the participants are explanation and offer of repair. Moreover, there was a statistically significant association between the independent variables (the participants’ age, gender, and level of education) and the choice of apology strategies. However, such an association was only significant for some discourse situations; e.g., in interaction with relatives that are in an equal status with the participant and in an adult-child interaction where the participant has a superior status.